The struggle for order : hegemony, hierarchy, and transition in post-Cold War East Asia - Goh, Evelyn (Oxford : Oxford University Press, 2014)
Arguing that existing ideas about balance of power and power transition are inadequate, this book gives an innovative reinterpretation of the changing nature of U.S. power, focused on the'order transition' in East Asia.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on November 5, 2013).
Keywords: Hegemony -- United States; United States -- Foreign relations -- East Asia; East Asia -- Foreign relations -- United States; United States -- Foreign relations -- 1989-